Dynamics and thermodynamics of the coronene octamer described by coarse-grained potentials. Issue 3 (22nd December 2016) - Hernández-Rojas, J.; Calvo, F.; Niblett, S.; Wales, D. J.
Abstract : Coarse-grained models developed for polycyclic aromatic hydrocarbons based on the Paramonov–Yaliraki potential have been employed to investigate the finite temperature thermodynamics, out-of-equilibrium dynamics, energy landscapes, and rearrangement pathways of the coronene octamer. Abstract : Coarse-grained models developed for polycyclic aromatic hydrocarbons based on the Paramonov–Yaliraki potential have been employed to investigate the finite temperature thermodynamics, out-of-equilibrium dynamics, energy landscapes, and rearrangement pathways of the coronene octamer. Molecular dynamics simulations are used to address the short-time behaviour, diffusion properties, convergence to equilibrium, and dissociation kinetics. A kinetic transition network composed of a connected database of stationary points provides a consistent picture of the complex potential and free energy landscapes, and enables us to describe rearrangements occurring over long time scales and associated thermal properties. Comparison with reference simulations performed with an all-atom description, indicates satisfactory agreement at moderate energies, especially when quadrupole corrections to the intermolecular potential are included. At higher energies, unimolecular evaporation rates are particularly well reproduced by the coarse-grained model. The potential energy landscapes exhibit multiple funnels for all the models, with alternative columnar arrangements competing at low energy. Entropy-driven structural transitions are predicted to involve largely cooperative motion, with entire stacks shifting and rotating around one another. These structural transitions, which were not characterised in earlier parallel tempering Monte Carlo simulations, are well represented by the coarse-grained models, with similar barrier heights but fewer steps.